Repolitics: literacy, new media and citizenship - Di Fátima, Branco (2013)
This article examines how new media literacy can contribute to citizen choice at election time and how the websites of legislative power help, or not, to form a solid opinion about politicians who, in the future, will try the re-election. In the last section we briefly review the Project Repolítica, a website that uses the collective choice of its users to build the profile of Brazilian politicians.